THE CONSCIENCE’S LENS ON ETHICAL DECISION MAKING IN A PLURALISTIC SOCIETY - Msogoya, Prospa (Journal of Learning on History and Social Sciences, 2025)
Objective: This paper explores the role of conscience as a central lens through which individuals navigate moral dilemmas in such a complex environment (Pluralistic society) and also the study highlights how conscience enables individuals to remain authentic to their values while engaging empathetically with others. Method: The paper used carefully reading as source of information and secondary data guided by the research theory of “W.D. Ross’s theory of prima facie duties” as a suitable guide in decision making in a pluralistic society where there are different beliefs, views, perceptions, ideologies, and culture. Results: It has been found that decision making based on utility, deontological (duty-based decisions), and teleological (end results-based decisions) does not foster ethical decisions that are both personally authentic and socially inclusive. Novelty: The study concludes that conscience should be treated as a vital, context-sensitive guide that grounds personal integrity while remaining open to public critique. Also, the study recommends that individuals must cultivate reflective conscience through moral education, exposure to diverse perspectives, and practices of humility and accountability for ethical decisions in a pluralistic society.